1998
DOI: 10.1021/jp981028o
|View full text |Cite
|
Sign up to set email alerts
|

Chemisorbed Oxygen on Au(111) Produced by a Novel Route:  Reaction in Condensed Films of NO2 + H2O

Abstract: We report a facile, low-temperature reaction between condensed-phase NO 2 and H 2 O that leads ultimately to the formation of a large concentration (θ 0 ) 0.42 monolayers) of adsorbed oxygen adatoms on a Au(111) surface. This reaction represents a novel route to generate surface oxygen on Au that can be utilized in fundamental studies of oxidation catalysis over Au such as low-temperature CO oxidation and the operation of Au converter tubes used in redox chemiluminesence detectors for atmospheric NO x . Also, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
74
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 16 publications
(30 reference statements)
8
74
1
Order By: Relevance
“…Based on their calibration, the maximum coverage of oxygen atoms deposited using our method was calculated to be~0.4 ML. This value is close to the saturation coverage of atomic oxygen deposited from the reaction of NO 2 and H 2 O (h O = 0.42 ML), [39] but less than that obtained from ozone exposure (h O = 1.2 ML) [41]. We corroborate the coverage estimate with temperature programmed desorption measurements of O 2 yields relative to those measured for a saturation coverage of atomic oxygen from ozone exposure.…”
Section: Interaction Of Sulfur and Oxygen With Au(111) At Low Coveragesupporting
confidence: 68%
See 1 more Smart Citation
“…Based on their calibration, the maximum coverage of oxygen atoms deposited using our method was calculated to be~0.4 ML. This value is close to the saturation coverage of atomic oxygen deposited from the reaction of NO 2 and H 2 O (h O = 0.42 ML), [39] but less than that obtained from ozone exposure (h O = 1.2 ML) [41]. We corroborate the coverage estimate with temperature programmed desorption measurements of O 2 yields relative to those measured for a saturation coverage of atomic oxygen from ozone exposure.…”
Section: Interaction Of Sulfur and Oxygen With Au(111) At Low Coveragesupporting
confidence: 68%
“…Recently, Mullins and coworkers deposited oxygen atoms on Au(111) using a supersonic beam of oxygen atoms produced from a radio frequency-generated plasma source [37]. Atomic oxygen has also been prepared on Au(111) by exposure to ozone (O 3 ), [16] thermal dissociation of gaseous O 2 using hot filaments, [38] O + sputtering, [15] and co-adsorption of NO 2 and H 2 O [39]. More recently, we developed a new method for depositing atomic oxygen on Au(111) by electron bombardment of NO 2 condensed on the Au(111) surface [40].…”
Section: Interaction Of Sulfur and Oxygen With Au(111) At Low Coveragementioning
confidence: 99%
“…This isomerization is known to occur in solid matrices at low temperatures or high pressures, on ice and in solution, 101,[135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150] (although one study 151 observed only the symmetric form of N 2 O 4 on ice films). Koel and coworkers [148][149][150]152 proposed that this isomerization occurs via the free O-H groups on amorphous ice, and it is possible that a similar process occurs in the thin films studied here. Once formed, the asymmetric ONONO 2 Experimental and theoretical studies [153][154][155] of the reactions of gas phase clusters of hydrated NO + show that reaction to generate HONO occurs with four or more water molecules bound to NO + .…”
Section: Mechanisms and Modelsmentioning
confidence: 99%
“…[70][71][72] In the case of HONO, the relatively large enthalpy of adsorption on the surface relative to water as discussed above suggests that the adsorbed species might already be partially or fully ionized.…”
mentioning
confidence: 98%